(untitled) (The Review of Diabetic Studies, 2025)
Social determinants of health (SDOH) play a critical role in shaping health outcomes and perpetuating health disparities among urban populations. This paper examines the multifaceted relationship between social determinants and health inequities, focusing on key factors including socioeconomic status, education, housing conditions, food security, and access to healthcare services. Through a comprehensive review of current literature and empirical evidence, this study demonstrates that structural inequalities embedded within urban environments significantly contribute to differential health outcomes across demographic groups. The analysis reveals that individuals living in disadvantaged urban neighborhoods experience higher rates of chronic diseases, mental health disorders, and premature mortality compared to their counterparts in more affluent areas. This paper argues that addressing health disparities requires a multi-sectoral approach that targets the root causes of inequality rather than merely treating disease symptoms. Policy recommendations include investing in affordable housing, improving educational opportunities, expanding access to nutritious food, and implementing community-based health interventions. The findings underscore the urgent need for public health practitioners, policymakers, and community stakeholders to collaborate in creating equitable urban environments that promote health and well-being for all residents.